Optimalisasi Peran Mahasiswa Kkn Dalam Bidang Peningkatan Pendidikan Di Desa Kangkung - Risma Sintiya Dewi; Pramita Khanifatul; Muhammad Akhdan; Den Ayu; Elinda Novita Dewi; Midian Savella; Herxi Thovan; Kasmuri Kasmuri (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2024)
Education is a crucial element in developing an individual's potential and intelligence. To carry out education effectively, teachers are needed who can teach in both formal and non-formal contexts. Our Community Service Program (KKN) was conducted in Kangkung Village, Kangkung District, with the main objective of providing community service and supporting the improvement of children's education in the village. Although the enthusiasm and learning spirit of the children in Kangkung Village is very high, the shortage of teaching staff is a major obstacle in achieving maximum education. This article is entitled "Optimizing the Role of KKN Students as Teachers in Improving Education in Kangkung Village." This research uses the Participatory Action Research (PAR) method and conducts field observations to identify potential and problems in the village. The results of KKN activities provide an overview of the enthusiasm and enthusiasm of children and the community for the role of students as teaching staff in supporting education in Kangkung Village through various formal and non-formal education activities carried out by KKN Group 114.